2016
DOI: 10.1111/joss.12206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Receptacle on the Expected Flavor of a Colored Beverage: Cross‐Cultural Comparison Among French, Japanese, and Norwegian Consumers

Abstract: The present online study was designed to investigate whether the expected flavor associated with a colored beverage is affected by the type of receptacle in which the drink is presented. More than 400 participants from France, Japan and Norway viewed photographs of red, green, yellow, blue, orange, brown and clear beverages presented in a water glass, a wine glass, a cocktail glass or a plastic cup. They had to indicate the first flavor that came to mind by choosing a flavor from a list of 24 options, and to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Furthermore, they found that flavor discrimination was impaired by coloring solutions inappropriately [ 29 ]. Wan et al [ 30 ] reported that the type of receptacle (water glass, wine glass, cocktail glass or plastic cup) modulated the expected flavor of a colored beverage. Color–flavor associations may be product-specific and have often been studied in beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that flavor discrimination was impaired by coloring solutions inappropriately [ 29 ]. Wan et al [ 30 ] reported that the type of receptacle (water glass, wine glass, cocktail glass or plastic cup) modulated the expected flavor of a colored beverage. Color–flavor associations may be product-specific and have often been studied in beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Culture and prior experience undoubtedly play an important role in determining our perception (e.g., see Bremner, Caparos, Davidoff, de Fockert, Linnell, & Spence, 2013 [5]; Van Doorn, Woods, Levitan, Wan, Velasco, Bernal-Torres, & Spence, 2017 [6]; Wan, Woods, Jacquot, Knoeferle, Kikutani, & Spence, 2016 [7]; Wan, Woods, Seoul, Butcher, & Spence, 2015 [8]). Indeed, a number of studies have demonstrated that people tend to rate drinks more favourably when they are presented in receptacles that are judged as being congruent (given their prior experience) with the contents, relative to when the same drink is presented in a receptacle that is deemed to be incongruent with the contents (Raudenbush, Meyer, Eppich, Corley, & Petterson, 2002 [9]; Schifferstein, 2009 [10]; see also Cardello, Maller, Masor, Dubose, & Edelman, 1985 [11]).…”
Section: Assessing the Role Of Culture And Congruency On The Impact Omentioning
confidence: 99%
“…Several studies have provided evidence for expectancy effects on sensory qualities of food and overall liking (Ares, Barreiro, Deliza, Gimenez, & Gambaro, ; Deliza & MacFie, ; Laureati, Conte, Padalino, Del Nobile, & Pagliarini, ). Sensory related expectancy effects have been found for specific external attributes such as the visual presentation of food (Paakki, Sandell, & Hopia, ; Tu, Yang, & Ma, ; Van Doorn, Colonna‐Dashwood, Hudd‐Baillie, & Spence, ), information about production practices and process (De Souza, Minim, Minim, Coimbra, & Da Rocha, ; Musto, Cardinale, Lucia, & Faraone, ), packaging‐related characteristics (Ares & Deliza, ; Maggioni, Risso, Olivero, & Gallace, ; Vidal, Barreiro, Gómez, Ares, & Giménez, ; Wan et al, ), price (Just, Siğirci, & Wansink, ), label appearance (Arcia, Curutchet, Costell, & Tárrega, ), and brand name (Di Monaco, Cavella, Iaccarino, Mincione, & Masi, ). For the case of wine tasting, Siegrist and Cousin () showed that such information affects the sensory experience itself and not only participants' overall assessment of the wine after the tasting.…”
Section: Introductionmentioning
confidence: 99%